2019
DOI: 10.1371/journal.pone.0223281
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome profiling of the onion thrips, Thrips tabaci Lindeman (Thysanoptera: Thripidae)

Abstract: The gut microbial community structure of adult Thrips tabaci collected from 10 different agro-climatically diverse locations of India was characterized by using the Illumina MiSeq platform to amplify the V3 region of the 16S rRNA gene of bacteria present in the sampled insects. Analyses were performed to study the bacterial communities associated with Thrips tabaci in India. The complete bacterial metagenome of T. tabaci was comprised of 1662 OTUs of which 62.25% belong to known and 37.7% of unidentified/unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes were found to be the most abundant bacterial phyla. Those groups are dominant in microbiota profiles of different insect species [ 54 , 55 , 56 ], and were also the most abundant in bacterial communities associated with other thrips, e.g., Hoplothrips carpathicus [ 57 ], Scirtothrips dorsalis [ 58 ], Thrips palmi [ 56 ], and T. tabaci [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes were found to be the most abundant bacterial phyla. Those groups are dominant in microbiota profiles of different insect species [ 54 , 55 , 56 ], and were also the most abundant in bacterial communities associated with other thrips, e.g., Hoplothrips carpathicus [ 57 ], Scirtothrips dorsalis [ 58 ], Thrips palmi [ 56 ], and T. tabaci [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To decode the functional implications of these gut symbionts, it is necessary to study their distribution. Thus, we have summarized recent metagenomics studies (whole insect and insect gut) of several insect pests which is demonstrated by phylum wise composition of bacteria in Figure 1A ( Yong et al, 2017 ; Tokuda et al, 2018 ; Bozorov et al, 2019 ; Gawande et al, 2019 ; Shah et al, 2020 ; Asimakis et al, 2021 ; Deguenon et al, 2021 ; He et al, 2021 ; Tegtmeier et al, 2021 ; Yu et al, 2021 ; Csorba et al, 2022 ; Li S. et al, 2022 ; Majumder et al, 2022 ; Wang et al, 2022 ). We have noticed with taken examples that Proteobacteria, Firmicutes and Actinobacteria were the most dominant phyla present in the insect gut could be due to their diverse roles in nutrition.…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%
“…To identify bacteria and fungi present in the samples, metagenomic sequences needed to be filtered for quality, aligned into contigs and compared to existing sequence databases (Gawande et al, 2019). Sequences were run through Trimmomatic 0.36 (Bolger et al, 2014) to remove low-quality base pairs, sequencing adapters and reads shorter than 100 bp; the following parameters were used: SLIDINGWINDOW 4:15 MINLEN: 36.…”
Section: Analysis Of the Soil Microbial Communitymentioning
confidence: 99%